Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian Mobil Merek Wuling di Kota Makassar dengan Minat Beli Sebagai Variabel Intervening - Nuha, Muhammad Saifin; amir, amir; Suhartini, Eka (Study of Scientific and Behavioral Management, 2022)
This study aims to determine the effect of product quality and price on purchasing decisions with purchase intention as an intervening variable for users of Wuling cars in Makassar City. This study uses primary data by taking data from questionnaires. The sampling technique in this study was probability sampling so that the number of samples used was 157 people. The data analysis technique in this study used (SEM) structural equation modeling with the help of smartPLS to be able to solve the problems and hypotheses that have been formulated in this study and used to test the relationships between variables. The results of this study indicate that Product Quality has no effect on Purchase Decision, Price has no effect on Purchase Decision, Product Quality has a significant effect on Purchase Intention, Price has a significant effect on Purchase Intention, Purchase Interest has significant influence on Purchase Decision, Product Quality has a significant effect significant effect on Purchase Decision through Purchase Interest and Price has no effect on Purchase Decision through Purchase Interest.